Tanggung Jawab Pidana Rumah Sakit Terhadap Pengelolaan Limbah Medis B3 Yang Meningkat Selama Pandemi Covid-19 Criminal Responsibility of Hospital Against Medical Toxic and Hazardous Waste Management That Increases During Covid-19 Pandemic - Devi Oktamala (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
All types of all living and non-living creatures that are inhabiting this earth and including from the interior of this earth is an explanation of the term commonly referred to as the living environment. With the development of the era until now the world is experiencing an era called the Covid-19 pandemic, it is still often found that humans do not pay attention and understand that the environment has a very important role and this understanding is needed by all humans because of the attention and understanding of humans towards the environment. Life raises a consequence and action in the form of environmental management as a guide for managing various kinds of waste from factories, hospitals and daily waste. In particular, it is located in hospitals, which in this pandemic era produced more waste than before, which increased up to four times from before this pandemic, such as the use of medical equipment and equipment used to treat and treat patients infected with covid 19 which became waste categorized as toxic and hazardous waste. Through legal issues, one problem formulation was drawn, namely How is the hospital's criminal responsibility for toxic and hazardous medical waste management according to the provisions of Legal number. 32 of 2009 concerning the protection and management of the environment. This research method uses normative legal research using three legal approaches, namely the statutory approach, conceptual approach, and case study. Based on the findings of this study, even though there are non-natural disasters, namely Covid-19, criminal responsibility must still exist or be enforced. However, the criminal provisions contained in a regulation can be a last resort, given the current urgent situation. constitution number 32 of 2009 concerning the Protection and Management of the Environment became the last means. This is also in accordance with the ultimum remedium principle which is one of the principles contained in Indonesian criminal law which states that criminal law should be used as a last resort in terms of law enforcement.